Cat Figures Using Assemblage Techniques as an Idea for Creating Two-Dimensional Artworks - Ayu Widari Syahfitri; Agus Priyatno; Adek Cerah Kurnia Azis (V-art: Journal of Fine Art, 2025)
The process of creating this artwork is closely connected to the artist’s personal experiences. An emotional attachment to cats serves as a significant source of inspiration in the creative process. The primary aim of this study is to describe the creative process involved in visualizing cat figures as an artistic idea through two-dimensional artworks employing an assemblage approach. This creation process adopts Alma M. Hawkins’ method as a reference for the stages of producing collage-based works, consisting of exploration, experimentation, and realization. The exploration stage involves direct data collection through observation and literature review. The subsequent stage, experimentation, includes developing drawing patterns and beginning to experiment with the assemblage forms and techniques employed. The final stage, realization, encompasses executing the work according to the established design until the finishing process is completed. The distinctive characteristics of cats inspire collage artworks that utilize assemblage techniques, mixed media, and materials such as clay, tissue paper, and magazine cuttings. These artworks depict the daily behaviors of cats on 50 × 60 cm canvases. The final output consists of three pieces that portray various behaviors, myths, and beliefs associated with cat figures, which can be interpreted in relation to human life.